Integral-type sliding mode fault-tolerant control for attitude stabilization of spacecraft - Zhu, Senqiang (2015)
Two fault-tolerant control (FTC) schemes for spacecraft attitude stabilization with external disturbances are proposed in this brief. The approach is based on integral-type sliding mode control strategy to compensate for actuator faults without controller reconfiguration. First, a basic integral-type sliding mode FTC scheme is designed so that sliding manifold can be maintained from the very beginning. Once the system enters the sliding mode, the dynamics of the closed-loop system with actuator fault is identical to that of the nominal healthy system. Second, the integral-type sliding mode fault-tolerant controller is incorporated with adaptive technique to accommodate actuator faults so that the required boundary information can be relaxed. The effectiveness of the proposed schemes against actuator faults is demonstrated in simulation.